Comparative transcriptomic analysis-based identification of the regulation of foreign proteins with different stabilities expressed in Pichia pastoris - Niu, Tingting; Cui, Yi; Shan, Xu; Qin, Shuzhen; Zhou, Xuejie; Wang, Rui; Chang, Alan; Ma, Nan; Jing, Jingjing; He, Jianwei (Frontiers in Microbiology, 2022)
The industrial yeast Pichia pastoris is widely used as a cell factory to produce proteins, chemicals, and advanced biofuels. In our previous study, we reported the construction of P. pastoris strains that overexpress a kind of molecular chaperone, protein disulfide isomerase (PDI), for improving the expression of exogenous proteins. Chicken cystatin (cC) is a highly thermostable cysteine protease inhibitor and a homologous protein of human cystatin C (HCC). In this study, wild-type cC and two mutants (amyloidogenic I66Q and a truncated protein ΔW lacking the α-helix 2) representing model proteins with different degrees of stability were expressed in P. pastoris GS115 strains without and with the overexpression of PDI. In addition to the endoplasmic reticulum quality control system represented by molecular chaperones, transcriptomic profiling was performed to compare the strains expressing exogenous proteins with different stabilities. Pichia pastoris that overexpressed PDI was able to increase the extracellular expression of the three proteins, indicating that overexpression of PDI could prevent the misfolding of unstable proteins or promote the degradation of the misfolded proteins to some extent. On this basis, we then explored the changes in other main signaling pathways and cell components in P. pastoris in response to intracellular folding stress caused by the expression of foreign proteins with different stabilities. For P. pastoris cells that expressed the I66Q or ΔW mutants, GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses of the common DEGs in these cells revealed significant upregulation of the genes involved in protein processing, but significant downregulation of the genes enriched in the Ribosome, TCA and Glycolysis/Gluconeogenesis pathways. This suggested that cells need to regulate their metabolism to increase the expression of foreign proteins in the growth and expression stages. Further hunting for hub genes indicated that the most downregulated ribosome protein, C4QXU7 in this case, might be an important target protein that could be manipulated to increase the expression of foreign proteins, especially proteins with a certain degree of instability.